ChemInform Abstract: Cobalt‐Catalyzed Electrophilic Cyanation of Arylzinc Halides with N‐Cyano‐N‐phenyl‐p‐methylbenzenesulfonamide (NCTS). Issue 15 (24th March 2016) - Cai, Yingxiao; Qian, Xin; Rerat, Alice; Auffrant, Audrey; Gosmini, Corinne
Abstract: The cobalt catalyst can be used for the synthesis of the intermediate organozinc species and for the coupling reaction.